2016
DOI: 10.1097/opx.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Induced Astigmatism on the Depth of Focus

Abstract: With an induced WTR astigmatism of -0.5 DC, the DoF can be enhanced in the near viewing distance with a marginal loss in binocular VA. The approach of using induced WTR astigmatism can lead to novel optical treatments for presbyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Although this is usually poorly tolerated postoperatively, the pinhole effect of the IC-8 may allow for refractive error to be compensated for, and may in fact help to enhance depth of focus as induced astigmatism has previously been reported to help enhance depth of focus for near vision. 19 The patient who received the AT Lisa IOLs (i.e., Case 4) presented postoperatively with fluctuating refraction, a common postoperative complication of RK, and postoperative myopia in both eyes; mean SE decreased from 1.875 D preoperatively to −1.75 D postoperatively. This overcorrection could be due to preoperative instability of the cornea and fluctuations in preoperative or postoperative refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is usually poorly tolerated postoperatively, the pinhole effect of the IC-8 may allow for refractive error to be compensated for, and may in fact help to enhance depth of focus as induced astigmatism has previously been reported to help enhance depth of focus for near vision. 19 The patient who received the AT Lisa IOLs (i.e., Case 4) presented postoperatively with fluctuating refraction, a common postoperative complication of RK, and postoperative myopia in both eyes; mean SE decreased from 1.875 D preoperatively to −1.75 D postoperatively. This overcorrection could be due to preoperative instability of the cornea and fluctuations in preoperative or postoperative refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Leube et al 22 reported that residual astigmatism could affect the subjective depth of focus. He concluded that with an induced WTR astigmatism of −0.5 D, the depth of focus could be enhanced in the near viewing distance with a marginal loss in binocular visual acuity (VA).…”
Section: Discussionmentioning
confidence: 99%
“…Participants wore their distance correction in a trial frame (UB4, Oculus, Germany) corrected for a viewing distance of 5 m. To evaluate the subjective depth of focus, defocus curves of high contrast visual acuity in a dioptric range of ± 1.50 D within 0.5 D steps were measured. The method to calculate the depth of focus from subjective obtained defocus curve was described elsewhere 37 . In brief, DoF is defined as the horizontal dioptric range at the threshold level of + 0.1 logMAR below the maximum value of visual acuity.…”
Section: Methodsmentioning
confidence: 99%